Comparative Evaluation of Bone-Supported Arch Bar vs Tooth-Supported Arch Bar in Mandibular Fracture Treatment - Motiwale, Tejas; Godase, Sandip; Agrawal, Nikit; V Mitra, Geeti; R. Vyas, Susmitha; Bhatt, Vaibhav (Journal of Neonatal Surgery, 2025)
Background: Maxillofacial trauma, increasingly common due to road travel and socio-economic activities, frequently involves mandibular fractures. Effective treatment requires precise reduction and fixation to restore occlusion. Aim: To compare the efficacy of bone-supported (Hybrid) vs tooth-supported (Conventional) arch bars in mandibular fracture management. Materials and Methods: This study, conducted at Sri Aurobindo College of Dentistry, included 28 patients with isolated mandibular fractures, divided equally into two groups. Group A (Hybrid arch bar): 13 males, 1 female. Group B (Conventional arch bar): 12 males, 2 females. Parameters assessed included placement/removal time, oral hygiene, complications, and stability. Results: Group A showed significantly faster placement and removal times. Average difference in removal time was 9 minutes and for placement is 30 minutes. Oral Hygiene Index (OHI) scores were better in Group A on the 28th postoperative day. Root perforation and mucosal coverage over screws were observed in Group A; glove perforations were more frequent in Group B. Conclusion: Hybrid arch bars offer a viable alternative to conventional ones, with improved fixation time and hygiene outcomes, though with specific complications to consider.